Reductive capacity measurement of waste forms for secondary radioactive wastes - Um, Wooyong; Yang, Jung-Seok; Serne, R. Jeffrey; Westsik, Joseph H. (Journal of nuclear materials, 2015)
The reductive capacities of dry ingredients and final solid waste forms were measured using both the Cr(VI) and Ce(IV) methods and the results were compared. Blast furnace slag (BFS), sodium sulfide, SnF2, and SnCl2 used as dry ingredients to make various waste forms showed significantly higher reductive capacities compared to other ingredients regardless of which method was used. Although the BFS exhibits appreciable reductive capacity, it requires greater amounts of time to fully react. In almost all cases, the Ce(IV) method yielded larger reductive capacity values than those from the Cr(VI) method and can be used as an upper bound for the reductive capacity of the dry ingredients and waste forms, because the Ce(IV) method subjects the solids to a strong acid (low pH) condition that dissolves much more of the solids. Because the Cr(VI) method relies on a neutral pH condition, the Cr(VI) method can be used to estimate primarily the waste form surface-related and readily dissolvable reductive capacity. However, the Cr(VI) method does not measure the total reductive capacity of the waste form, the long-term reductive capacity afforded by very slowly dissolving solids, or the reductive capacity present in the interior pores and internal locations of the solids. •Reduction capacities is important for redox sensitive radionuclide release.•Correct measurement of reduction capacity is necessary for waste form capacity.•Ce(IV) method should be used for total reduction capacity of waste form.•Blast furnace slag is a major source of reduction in cementitious waste form.•Additional getters can be used to increase reduction capacity in waste form.